2011
DOI: 10.1371/journal.pone.0022947
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Utilizing Different Optical Coherence Tomography Devices for Clinical Purposes and in Multiple Sclerosis Trials

Abstract: Optical coherence tomography (OCT) derived retinal measures, particularly peri-papillary retinal nerve fiber layer (RNFL) thickness, have been proposed as outcome measures in remyelinating and neuroprotective trials in multiple sclerosis (MS). With increasing utilization of multiple centers to improve power, elucidation of the impact of different OCT technologies is crucial to the design and interpretation of such studies. In this study, we assessed relation and agreement between RNFL thickness and total macul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 66 publications
0
56
0
Order By: Relevance
“…10,11 Peripapillary and macular data were obtained with the Optic Disc Cube 200 3 200 and Macular Cube 512 3 128 protocols, respectively. Experienced technicians performed optical coherence tomography (OCT) scans, which were monitored to ensure reliable fixation.…”
Section: Optical Coherence Tomography Retinal Imaging Was Per-mentioning
confidence: 99%
“…10,11 Peripapillary and macular data were obtained with the Optic Disc Cube 200 3 200 and Macular Cube 512 3 128 protocols, respectively. Experienced technicians performed optical coherence tomography (OCT) scans, which were monitored to ensure reliable fixation.…”
Section: Optical Coherence Tomography Retinal Imaging Was Per-mentioning
confidence: 99%
“…Retinal imaging was performed using Cirrus HD-OCT (model 4000) with software version 5.0 (Carl Zeiss Meditec, Dublin, CA), as described in detail elsewhere. 26 Peripapillary data were obtained with the Optic Disc Cube 200 3 200 protocol. Macular data were obtained using the Macular Cube 512 3 128 protocol.…”
mentioning
confidence: 99%
“…There are significant differences among commercially available OCT devices in RNFL thickness measurements in patients with ON and/or relapsingremitting multiple sclerosis, so that RNFL measurements cannot be directly compared. [3][4][5][6] Clinicians should be aware that measurements are generally higher with Stratus than with Cirrus, 4,5 except at thinner RNFL values, and slightly higher on Spectralis compared to Cirrus OCT. 3,6 OCT provides information on probable RNFL defects as 4 color codes through comparison of the RNFL profile with an internal age-matched normative database. Recently, Kim and associates 7 evaluated the color-code agreement between Cirrus and Stratus OCT in patients with glaucoma, and they concluded that color codes were not interchangeable.…”
mentioning
confidence: 99%